2015
DOI: 10.1111/jns.12120
|View full text |Cite
|
Sign up to set email alerts
|

The Val30Met familial amyloid polyneuropathy specific Rasch‐built overall disability scale (FAP‐RODS©)

Abstract: Familial amyloid polyneuropathy (FAP) is a chronic debilitating multi-organic disorder, mainly assessed using ordinal-based impairment measures. To date, no outcome measure at the activity and participation level has been constructed in FAP. The current study aimed to design an interval activity/participation scale for FAP through Rasch methodology. A preliminary FAP Rasch-built overall disability scale (pre-FAP-RODS) containing 146 activity/participation items was assessed twice (interval: 2-4 week; test-rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Measure of QOL related to activities of daily living: R-ODS R-ODS measures activities of daily living and captures the ability of an individual to function independently in daily life [20,45]. The 24-item R-ODS measures limitations in usual daily activities and social participation [16,29,46].…”
Section: Eq-vasmentioning
confidence: 99%
See 1 more Smart Citation
“…Measure of QOL related to activities of daily living: R-ODS R-ODS measures activities of daily living and captures the ability of an individual to function independently in daily life [20,45]. The 24-item R-ODS measures limitations in usual daily activities and social participation [16,29,46].…”
Section: Eq-vasmentioning
confidence: 99%
“…This subsequently impacts the patients' abilities to complete everyday tasks, work and attend social functions. Among the disease symptoms, neuropathy manifests as pain, sensation loss, weakness and reduced mobility, and can significantly impair patients' abilities to perform activities of daily living such as buttoning a shirt or turning a key in a lock [20]. Autonomic dysfunction leads to orthostatic intolerance and debilitating GI symptoms that are associated with loss of consciousness and extreme constipation and diarrhea, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One important example involves transthyretin familial amyloid polyneuropathy (TTR‐FAP) . The results of recent randomized clinical trials of tafamidis and diflunisal showed benefits in patients with TTR‐FAP on ClinRO and PRO measures, for example, the Norfolk QOL‐DN; in addition, Rasch‐built symptom and disability measures have been developed for use in future clinical trials . These recent studies of TTR‐FAP have the potential to be used as models to address challenging issues in clinical trial design and the development of novel PROs for disease‐modifying treatments for the peripheral neuropathies we have discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Val30Met Familial Amyloid Polyneuropathy Specific Rasch-Built Overall Disability Scale (FAP-RODS) is a 34-item, disease-specific interval measure suitable for detecting activity and participation restrictions in patients with ATTRv amyloidosis [20].…”
Section: Patient-reported Aspects and Quality Of Life Measuresmentioning
confidence: 99%